A CRITIQUE OF TRADITIONAL PEDAGOGICAL METHODS IN THE TEACHING OF ENGLISH LANGUAGE SKILLS - Cecilia Titiek Murniarti (Celt: A Journal of Culture, English Language Teaching & Literature, 2008)
This paper is a critique of traditional pedagogical method in the teaching of English skills. In Indonesia. the emphasis of the teaching of English skill is on preparing students for jobs and standardized tests. While these purposes are necessary to improve students' language fluency. they are insufficient to equip students with skills they need to perform beyond college life. This paper argues that the focus of English teaching in college should be on the improvement of higher order thinking skills and the fostering of self-authorship. The paper uses socio-cultural theories of learning to discuss self-authorship and offers pedagogical implications on the basis of those theories.